Prevalence and characterization of methicillin-resistant Staphylococcus aureus among healthy children in a city of Argentina - Gardella, N. (2011)
Community acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) is a major global problem. Healthy carriers of S. aureus strains have an important role in the dissemination of this bacterium. The aim of this study was to estimate the prevalence of S. aureus and methicillin-resistant S. aureus (MRSA) carriage among healthy children in a city of Buenos Aires province, Argentina, and to determine the potential risk factors for its acquisition. We also described the molecular features of MRSA strains circulating in this population. S. aureus carriage was investigated in all children attending the last year of kindergarten during the 2008 school- year period. Household contacts of MRSA carriers were also screened. Of 316 healthy children, 98 (31.0%) carried S. aureus, including 14 MRSA carriers (4.4%) and 84 methicillin susceptible S. aureus (MSSA) carriers (26.6%). All MRSA isolates carried the SCCmec type IV cassette. Eight of the fourteen isolates were closely related to the clone responsible for most severe community- acquired MRSA infections caused in our country (CAA: PFGE A, SCCmec IV, spa t311, ST5). Two subtypes (A1 and A2) were distinguished in this group by PFGE. Both had agr type II and presented the same virulence determinants, except for PVL coding genes and sea that were only harbored by subtype A1. Our results, based on the analysis of MRSA isolates recovered in the screening of healthy children, provide evidence of a community reservoir of the major CA-MRSA clone described in Argentina.